Factors associated with newly diagnosed ischemic stroke among people with type 2 diabetes mellitus in Thailand: A population-based case-control study - Junjira Phasom; Ratchadaporn Ungcharoen; Pakorn Pusuwan; Nitikorn Phoosuwan (Narra J, 2025)
Stroke is a leading cause of mortality and disability-adjusted life years. Its incidence is rising across Asia, with ischemic stroke accounting for approximately 80% of total stroke cases in Thailand. Stroke often leads to long-term disabilities, including impairments in speech, communication, and cognitive function. The aim of this study was to investigate risk factors associated with newly diagnosed ischemic stroke. A matched case-control study was conducted, including 154 newly diagnosed ischemic stroke cases and 183 non-stroke controls, all with type 2 diabetes mellitus (T2DM). Data were collected between February and September 2022 (post-COVID-19 period) using a structured questionnaire covering socio-demographics, lifestyle factors, perceived social support, and self-care management (SCM). Multivariable logistic regression models were used to estimate adjusted odds ratios (aOR) with 95% confidence intervals (CI). The majority of participants were female (60.8%), Buddhist (92.9%), and agriculturists (66.5%), with a mean age of 58.9 (±9.9) years. Factors associated with ischemic stroke included male (aOR: 3.53; 95%CI: 1.73–7.21), Buddhism (aOR: 3.53, 95%CI: 1.11–11.25), sedentary occupation (aOR: 5.78; 95%CI: 2.61–12.81), and T2DM duration >10 years (aOR: 6.19, 95%CI: 3.55–10.80). Protective factors included age ≥60 years (aOR=0.55, 95%CI: 0.31–0.98) and moderate SCM levels (aOR=0.45, 95%CI: 0.26–0.80). This study highlighted that prolonged T2DM and sedentary occupations significantly contributed to ischemic stroke risk. Targeted prevention strategies, including lifestyle modifications and enhanced diabetes self-care management, may help reduce the burden of ischemic stroke.